Impaired Insulin Signaling Molecules in Triceps Muscle of Diethyl Hexyl Phthalate Treated Rat is Amelioreted by Antioxidant Vitamins - Balasubramanian, Karundevi (International Journal of Pharmaceutical & Biological Archive, 2017)
Available toxicological testing in animals and in vitro test, supported by limited human data, provide evidence linking Diethyl hexyl phthalate (DEHP) and its metabolites to a wide range of adverse effects in the reproductive tracts, liver, skeletal muscle, lungs, kidney and fetus. Recently there has been growing concern for the impact of plastic; polyvinylchloride (PVC) based endocrine disruptors like DEHP affects the function of endocrines and other organs in human beings and animals. Previous studies have shown that exposure to DEHP results in elevated level of blood glucose, decrease in serum insulin and testosterone level. However, specific effects of DEHP on insulin signaling molecules in triceps muscle; an organ involved in the regulation of glucose homeostasis has received only little attention. Healthy adult male albino rats of Wistar strain (Rattus norvegicus) were divided into four groups: Group I: Control; Groups II and III: DEHP treated (dissolved in olive oil at a dose of 10 and 100 mg/kg body weight, respectively, once daily through oral intubation for 30 days); and Group IV: DEHP (100 mg/kg body weight) plus vitamins E (50 mg/kg body weight) and C (100 mg/kg body weight) dissolved in olive oil and distilled water, respectively, once daily through oral intubation for 30 days. After the completion of treatments, animals were euthanized and perfused (whole body); triceps was dissected out and subjected to assessment of various parameters. Our results demonstrate that DEHP treatment induces ROS and lipid peroxidation. Furthermore, DEHP treatment significantly decreased the levels of insulin receptor, membrane GLUT4 protein as well as it reduces glucose uptake, oxidation and glycogen in skeletal muscle due to decreased serum insulin level. Antioxidant vitamins (C & E) have significant protective role against the adverse effect of DEHP on these tissues of adult male albino rat. All together, these results suggest that DEHP exposure induces lipid peroxidation which disrupts the membrane integrity and thus the insulin receptor and membrane GLUT4 proteins leading to reduced glucose oxidation in triceps muscle. Supplementation of vitamins (C & E) prevented the DEHP-induced changes.